Actinobaculum schaalii, a commensal of the urogenital area. (25th January 2013) - Olsen, Anne B.; Andersen, Pernille K.; Bank, Steffen; Søby, Karen Marie; Lund, Lars; Prag, Jørgen
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Actinobaculum schaalii is considered to be a part of the normai flora in the genital and urinary tract area. It has been associated to urinary tract infection (UTI), sepsis, osteomyelitis, endocarditis and Foumier's gangrene. So far it has mainly been isolated from urine, blood and pus, and predominantly in elderly patients. This study examined the habitat of A. schaalii by collecting samples from skin and urine in patients with kidney or ureter stones before and after treatment with Extracorporeal Shock Wave Lithotripsy (ESWL). Additionally faeces and vaginal swabs from routine specimen in patients not undergoing ESWL and without known urinary calculi were also analysed. The study does not find A. schaalii in faeces but shows it to be presents on skin and mucosa in the genital area. A. schaalii is also shown a possible pathogen in the stone‐patient group undergoing ESWL. Objective To study the habitat of Actinobaculum schaalii by examing groin swabs, faeces samples and vaginal swabs, and to determine whether it is a common uropathogen in patients with kidney or ureter stones. Patients and Methods A quantitative real‐time PCR assay was used to analyse all samples, which were collected between 2010 and 2011. A total of 38 patients (24 men and 14 women), with kidney or ureter stones and undergoing extracorporeal shock wave lithotripsy (ESWL), provided urine samples and had groin swabs taken. In addition, 30 faecal samples and 19 vaginal swabs that had been sent for routine microbiological examinations from patients outside the ESWL group were analysed. A chi‐squared test was used to analyse the differences between patient groups, studying samples from urine, faeces samples, groin swabs and vaginal swabs. Results Actinobaculum schaalii was found in the urine samples from 14 (37%) patients undergoing ESWL, and in both urine and groin swabs from seven (18%) patients. Actinobaculum schaalii was not found in faeces samples but it was found in six (32%) of the vaginal swabs, predominantly in patients >50 years (P = 0.06). Conclusion The study indicates that A. schaalii is a commensal found on skin, urine and vaginal mucosa in the human urogenital area and supports other investigations in its finding that the elderly are at greatest risk of being colonized with A. schaalii.